Analysis of Educational Curriculum Evolution in Indonesia and Its Impact on Increasing Education Quality - Raodatul Jannah (International Journal of Social Service and Research, 2023)
The evolution of the education curriculum in Indonesia has undergone significant changes in line with the times and global demands. This study aims to analyze the process of evolution of the education curriculum in Indonesia from the period 1947 to 2013, and identify its impacts on improving the quality of education. This research is a descriptive analysis research using a qualitative approach. The data collection technique was carried out by means of a literature review. The data that has been collected is analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The results of the research show that the evolution of the education curriculum in Indonesia has undergone many changes from time to time. These changes were made to adapt to the growing needs of society. Changes in the education curriculum in Indonesia have had a positive impact on improving the quality of education, this can be seen from the increased skills and competencies of students who are more in line with the demands of the times, by adopting a curriculum that is more relevant and responsive to social, technological and economic developments, students will have the opportunity to develop skills needed in the real world.